Effects of a noncircular chainring system on muscle activation during cycling - Dagnese, F.; Carpes, F. P.; de Assis Martins, E.; Stefanyshyn, D.; Bolli Mota, C. (Journal of Electromyography and Kinesiology, 2011)
Previous studies evaluated cycling with noncircular chainrings and suggested that changes in muscle activation would occur in response to altered pedaling mechanics throughout the crank arm revolution. However, no previous study addressed this question. The aim of this study was to compare the magnitude of muscular activity between a conventional and a noncircular crank system during an incremental maximal cycling test. Seven mountain-bike trained cyclists completed two incremental maximal tests, separated by 48 h, one for each crank system. Each test started with a workload of 100 W and was increased by 30 W every minute until exhaustion. Power output, pedaling cadence and heart rate were monitored and compared between the crank systems using paired t-tests. Surface EMG was recorded from the right rectus femoris, vastus medialis, biceps femoris and gastrocnemius medialis. EMG was compared using a general linear model considering as factors the crank system and workload with post hoc analysis at a = 0.05. RMS presented effect of workload, but no effect of crank system was found for the muscles analyzed. The present results do not support effects of the noncircular crank system on variables of performance and muscle activation during incremental cycling in trained mountain bike cyclists.